STRATEGI BERTAHAN HIDUP KELUARGA YANG MENIKAH DI USIA DINI DI DESA BUATAN BARU KECAMATAN KERINCI KANAN KABUPATEN SIAK - Eriani, Suci; Jalil, Ashaluddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village Buatan Baru Right Kerinci District of Siak which took place on 15 November 2014 to complete. The purpose of this study was to determine the factors that lead to marriage at an early age and to determine strategies used them in defending the lives of their families.To obtain the necessary data in this study, the authors collected data by descending directly to the location of the study or observation by spreading questioner and also conduct in-depth interviews. The data obtained were processed in the form of qualitative analysis.The conclusion of the study is the background adolescent marriages at an early age is the existence of internal and external factors. The internal factor is a factor of the inner self that is the willingness to do a wedding at an early age. While external factors are derived environment, economy, or the mass media. Family life is the responsibility of the head of the family although in this case occurred in the family who still early age or adolescence. Efforts to meet the needs of viable for family members to work or have other ways to survive. To survive must have a strategy, which is a careful plan of an activity to achieve the objectives have been agreed.Keywords: Marriage early age, Strategy survive.